2020
DOI: 10.20409/berj.2019.222
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Systemic Risks in the Turkish Banking Sector

Abstract: This paper focused on measuring the systemic risks in Turkey's banking sector by using two major measures that have been proposed in the literature as conditional value at risk (CoVaR) and marginal expected shortfall (MES). In order to compute the contribution of banking sector to systemic risks, the MES and ΔCoVaR measures are estimated for the six Turkish banks, which are listed, on the Borsa Istanbul (BIST) during 2000-2016 period by using Engle's dynamic conditional correlation model. The preliminary resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…In our study, we also find that Yapi Kredi, Akbank, Garanti, Isbank and TEB are identified as the most systemically important banks. Sengul and Yilmaz (2019) who ranked six Turkish banks based on their stock returns by using the CoVaR and MES methods. Finansbank, ICBC Turkey Bank, Yapi Kredi, Akbank, Garanti and Isbank were ranked according to their systemic risk contribution in descending order.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we also find that Yapi Kredi, Akbank, Garanti, Isbank and TEB are identified as the most systemically important banks. Sengul and Yilmaz (2019) who ranked six Turkish banks based on their stock returns by using the CoVaR and MES methods. Finansbank, ICBC Turkey Bank, Yapi Kredi, Akbank, Garanti and Isbank were ranked according to their systemic risk contribution in descending order.…”
Section: Resultsmentioning
confidence: 99%
“…Akkoyun et al (2013) measure the systemic importance of eight Turkish banks with contingent claims analysis and Shapley value without giving a name. Sengul and Yilmaz (2019) investigate the systemic risk of the Turkish banking sector by using CoVaR and marginal expected shortfall. The data includes six Turkish banks during 2000-2016 and included macroeconomic and financial market variables.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Alber [4]; Kleinow and Nell [9]; Khiari and Nachnouchi [10]), however, Hunjra, et al [6] and Weiß, et al [11] determined that larger banks tend to be associated with lower risk. In contrast to most studies considering leverage positively influencing bank risk (such as Anghelache and Oanea [12]; Borri, et al [13]; Sengul and Yilmaz [14]); Cicak [15] and Qin and Zhou [16] reached a result that less leveraged banks are connected to greater risk.…”
Section: Literature Reviewmentioning
confidence: 75%
“…Papanikolaou and Wolff [21] find a negative impact on economic growth and inflation on banking risk. While Sengul and Yilmaz [14] reveal a positive association between economic growth and risk measure. And according to Vallascas and Keasey [7], economic growth and inflation are insignificant.…”
Section: Idiosyncratic Risk Determinants and Hypothesismentioning
confidence: 88%